A Disparitas Putusan Hakim Dalam Perkara Tindak Pidana Penggelapan Dalam Jabatan: Disparitas Putusan Hakim dalam Perkara Tindak Pidana Penggelapan dalam Jabatan - Aprizal, Joni; Marlinah (UIR Press, 2025)
The research aims to examine the causes of disparity and the basis for judges' considerations in deciding cases of Embezzlement in Office with a focus on Decision Number: 31/Pid.B/2024/PN Bgl, Decision Number: 161/Pid.B/2024/PN Bgl and Decision Number 396/Pid.B/2024/PN Bgl. This research uses a normative juridical approach based on law, theories, principles and legal concepts. The legal materials used include primary, secondary, and tertiary legal materials. The results of the study indicate that the Defendant's actions fulfill the elements of Article 374 of the Criminal Code concerning embezzlement in office and the factors that cause disparity in judges' decisions are as follows: a. Factors of power and freedom of judges, b. Factors of evidence in court, c. Factors of judges' considerations in giving decisions, which consist of legal considerations and non-legal considerations, and d. Factors of uncertainty in sentencing guidelines